A theory for Indigenous Australian health and human service work : connecting Indigenous knowledge and practice. - Muller, Lorraine (Allen & Unwin : Made available through hoopla, 2014)
Most people of European background are not aware that they see the world through the lens of the Western tradition, but for Indigenous people, it can seem like a foreign language. Indigenous ways of thinking and working are grounded in many thousands of years of oral tradition, and continue among Australian Aboriginal and Torres Strait Island people today. Lorraine Muller shows that understanding traditional holistic approaches to social and emotional wellbeing is essential for practitioners working with Indigenous clients across the human services. She explores core principles of traditional Indigenous knowledge in Australia, including relatedness, Country, circular learning, stories, and spirituality. She then shows how these principles represent a theory for Indigenous practice. This book offers a deep insight into Indigenous Australian ways of working with people, in the context of a decolonization framework. It is an invaluable resource for both Indigenous and non-Indigenous practitioners and researchers in health, social work, community work, education, and related fields.